Kuliner sebagai Identitas Budaya dan Penggerak Ekonomi Kreatif Indonesia - Rina Pramudya Yolanda; Deswita Maharani; Amalia (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study aims to analyze the integration of local cultural identity in culinary innovation in creative villages and the effectiveness of supporting digital policies and strategies. Using a systematic thematic analysis of the latest literature, the results reveal that traditional value based culinary innovations developed through embedded social ecosystems and reciprocal mechanisms can strengthen community economies and adaptive capacities. Contextual policies such as the creative belt, supported by digital destination strategies, have proven to transform areas into competitive tourist destinations. In conclusion, culinary plays a dual role as an instrument of cultural preservation and a driver of sustainable economy, the success of which requires continuous synergy between transparent leadership, infrastructure support, stable funding, and government and community collaboration.